Word sense disambiguation for English Quranic IR system - Sabrina, Tiun; Zakr, Hamed; Masnizah, Mohd; Noor Azlinda, Zainal Abidin; Ahmad Irfan, Ikmal Hisham (IEEE, 2015)
Quranic text Information Retrieval (IR) is quite demanding yet very trivial due to that user will not always use the exact keywords to retrieve the relevant Quranic text (verse). Many have tried to overcome this problem by expanding or reformulating the query entered by users using semantic approaches with resources such as ontologies and thesauri. Word Sense Disambiguation (WSD) has been less interest to the IR research community due to the insignificant or very little significant impact on the IR performance. Recently, researchers pay interest on applying WSD to the IR problem due to the intuition that deep semantic analysis on the query process will give good impact on the IR performance. However, we have not seen any articles mentioning the use of WSD for Quranic IR, which we are assuming less or none research on WSD for Quranic IR have been carried out. Thus, this motivates us to explore WSD impact on Quranic IR performance. This paper will describe our on-going project on building an English Quranic WSD at the early stage, which is still at the proposal stage, where we layout what could be the best approach, resources and disambiguation algorithm for Quranic WSD for IR.